N-Acetylcysteine Improves Pancreatic Microcirculation and Alleviates the Severity of Acute Necrotizing Pancreatitis (Gut and Liver, 2013)
Background/AimsTo investigate the beneficial effect of N-Acetylcysteine (NAC) on pancreatic microvascular perfusion in acute necrotizing pancreatitis (ANP).Methods : Fifty-four rats were divided into a control group, an ANP group and an NAC-treated group. The ANP model was established by a retrograde injection of 3% sodium taurocholate into the pancreatic duct. The NAC-treated group received an intravenous infusion of NAC just 2 hours before and 30 minutes after the induction of ANP. The pancreatic microvascular perfusion was measured with laser Doppler flowmetry and pancreatic samples were collected for histological examination.Results : The microvascular perfusion in the NAC-treated group decreased slightly and exhibited a significant increase compared to the ANP group (p<0.01). A pathological examination revealed that edema and inflammatory infiltration decreased, and the hemorrhaging and necrosis of the pancreas were significantly reduced.Conclusion : sNAC could improve pancreatic microvascular perfusion and alleviate the severity of sodium taurocholate-induced ANP, possibly representing a new therapeutic approach to prevent the progression of ANP.